Clustering-triggered Emission of Cellulose and Its Derivatives - Du, Lin-Lin; Jiang, Bing-Li; Chen, Xiao-Hong; Wang, Yun-Zhong; Zou, Lin-Min; Liu, Yuan-Li; Gong, Yong-Yang; Wei, Chun; Yuan, Wang-Zhang (Chinese journal of polymer science, 2019)
In recent years, nonconventional luminogens free of aromatic groups have attracted extensive attention due to their academic importance and promising wide applications. Whilst previous studies generally focused on fluorescence from aliphatic amine or carbonyl-containing systems, less attention has been paid to room temperature phosphorescence (RTP) and the systems with predominant oxygen functionalities. In this work, photophysical properties of the polyhydroxy polymers, including microcrystalline cellulose (MCC), 2-hydroxyethyl cellulose (HEC), hydroxypropyl cellulose (HPC), and cellulose acetate (CA), were studied and compared. While MCC, HEC, and HPC solids showed bright emission alongside distinct RTP, CA demonstrated relatively low intensity of solid emission without noticeable RTP. Their emissions were explained in terms of the clustering-triggered emission (CTE) mechanism and conformation rigidification. Additionally, on account of its intrinsic emission, concentrated HEC aqueous solution could be used as the probe for the detection of 2,4,6-trinitrophenol (TNP).